Towards a Feminist Cinematic Ethics : Claire Denis, Emmanuel Levinas and Jean-Luc Nancy - Hole, Kristin Lene (Book collections on Project MUSE., 2015)
Develops an account of non-normative feminist cinematic ethics and a fresh methodological approach to film-philosophy. Towards a Feminist Cinematic Ethics develops an account of non-normative ethics that can be used to think about filmmaking and viewing, using two philosophers-Emmanuel Levinas and Jean-Luc Nancy, and the work of filmmaker Claire Denis. In an accessible and engaging manner, it offers new readings of Denis' films, situating them within larger feminist, postcolonial and queer debates about identity and difference. Using a generative methodology, the book works towards a mutually challenging and productive relationship between cinematic ideas and philosophical concepts. Key Features. Develops a generative methodology for theorizing a more mutually challenging and productive relationship between cinematic ideas and philosophical concepts Contributes to ongoing attempts to theorize a post-phenomenological, yet embodied account of spectatorship using Levinas and Nancy, both of whom are under-examined within film studies Articulates a philosophically rigorous account of non-normative ethics and applies it to filmmaking and viewing Offers new readings of Claire Denis' films and situates them within larger feminist, postcolonial and queer debates about identity and difference